Data mining systems for teaching - Kurasova, Olga (Lietuvos matematikos rinkinys, 2014)
Data mining systems suitable for data mining teaching have been investigated in the paper. Ussualy, such systems as SPSS Modeler (Clementine), Statistica, SAS/STAT are used in the mathematical statistics courses. However, they are not always suitable for data mining teaching. WEKA, Orange, KNIME, RapidMiner systems are more appropriate for this purpose.